Analisis Terhadap Putusan Mahkamah Agung Nomor 1557 K/Pdt/2019 Tentang Wanprestasi dalam Perjanjian Pengikatan Jual Beli Tanah - Zahra, Nayla Audi; Reyhan Prabowo, Nazwa Anvella Dilla,; Sabrina Aulia Amri, Rindy Antika Indraswara,; William Haposan Lubis, Sally Hania Hadi,; Zaharani, Zakia (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to examine the legal considerations applied by the Sidoarjo District Court, the Surabaya High Court, and the Supreme Court in resolving a land sale and purchase dispute between H. Suudhi and PT Jatarupa Prakarsa Jaya, as well as to analyze the impact of Supreme Court Decision No. 1557 K/Pdt/2019 on legal certainty in land sale and purchase agreements. This research employs a normative juridical method with statutory and case approaches. The findings indicate that the Supreme Court declared PT Jatarupa Prakarsa Jaya to be in default (wanprestasi) for failing to fulfill its obligations as stated in the Sale and purchase Binding Agreement (PPJB). The decision emphasizes that a PPJB executed legally before a notary possesses binding legal force and provides protection to parties acting in good faith, even though it does not yet result in a formal transfer of ownership as in a Sale and Purchase Deed (AJB). The implications of this ruling reinforce the application of the pacta sunt servanda principle and strengthen legal certainty in land sale and purchase practices in Indonesia.